The Yo-Yo IR2 test: physiological response, reliability, and application to elite soccer - Oberacker, L. M.; Davis, S. E.; Haff, G. G.; Witmer, C. A.; Moir, G. L. (The Journal of Strength and Conditioning Research, 2012)
The purpose of this study was to compare the effects of resistance training performed on either a stable or unstable surface on performance tests in female soccer players. Nineteen National Collegiate Athletic Association Division II female soccer players were assigned to either an unstable training group (UST: 19.0 ± 0.47 years; 1.69 ± 6.4 m; 67.8 ± 7.7 kg) or a stable training group (ST: 19.6 ± 0.49 years; 1.64 ± 3.2 m; 62.7 ± 6.27 kg). Player positions were distributed evenly between the groups. Both the groups followed a 5-week periodized resistance training program designed to develop maximum muscular strength. The groups performed the same exercises during each workout, with the UST performing 2 of the exercises in each session on an unstable surface. Pretraining and posttraining measures of straight-line sprint speed, planned and reactive agility, aerobic capacity, and countermovement vertical jump (CMJ) were taken. Significant main effects for time were reported for straight-line sprint speed, planned agility, and reactive agility with both groups demonstrating improvements during the posttraining testing session. The ST demonstrated a significant increase in CMJ during the posttraining session (change in mean: 0.04 m) in contrast to the decline demonstrated by the UST (change in mean: -0.01 m). Performing resistance training exercises on an unstable surface confers no advantage over traditional resistance training exercises for improving the speed, agility, and aerobic capacity of female soccer players. Furthermore, the use of an unstable surface may inhibit the effects of resistance training on vertical jump height, an important variable in soccer performance.